2009
DOI: 10.1124/dmd.108.023309
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the Breast Cancer Resistance Protein Expression and Function in Caco-2 Cells Using Lentiviral Vector-Based Short Hairpin RNA

Abstract: ABSTRACT:A series of stable breast cancer resistance protein (BCRP, ABCG2) knockdown cell lines were produced by transduction of Caco-2 cells with lentiviral vector-based short hairpin RNA (shRNA). Caco-2 cell is a human intestinal-derived cell line widely used to study intestinal drug absorption. Caco-2 expresses three apical drug efflux transporters: BCRP, P-glycoprotein (P-gp; ABCB1), and multidrug resistance protein 2 (MRP2, ABCC2). BCRP and P-gp in particular play a significant role in pharmacokinetics be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…One approach that could furnish unambiguous identification of transporter involvement is the use of RNA interference to knock down the expression of relevant transporters. This technique has already been used to selectively knock down the expression of BCRP, P-gp, and multidrug resistance-associated protein 2 in Caco-2 cells (Zhang et al, 2009), which proved valuable in elucidating the role of efflux transporters in the biliary efflux of ximelagatran (Darnell et al, 2010) and several statin drugs (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One approach that could furnish unambiguous identification of transporter involvement is the use of RNA interference to knock down the expression of relevant transporters. This technique has already been used to selectively knock down the expression of BCRP, P-gp, and multidrug resistance-associated protein 2 in Caco-2 cells (Zhang et al, 2009), which proved valuable in elucidating the role of efflux transporters in the biliary efflux of ximelagatran (Darnell et al, 2010) and several statin drugs (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the post-transcriptional gene silencing by RNA interference to specifically knock down drug transporters is a rapidly growing field of research (Celius et al, 2004;Hua et al, 2005;Tian et al, 2005;Watanabe et al, 2005;Li et al, 2006;Yue et al, 2009;Zhang et al, 2009). Even though siRNA and shRNA have emerged as powerful tools to study gene function in a sequence-specific manner, off-target effects have been observed in several studies (Jackson et al,FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus plasmid vectors containing shRNA inserts targeting human P-gp (GenBank accession number NM_000927) and MRP2 (GenBank accession number NM_000392) genes were obtained from Sigma-Aldrich. The transduction procedure was described previously (Zhang et al, 2009). In brief, the cells were plated in 96-well tissue culture plates at a density of 5 ϫ 10 6 cell/well and transduced with 1 g of P-gp-or MRP2-targeting shRNA viral vector.…”
Section: Methodsmentioning
confidence: 99%
“…However, there still remain some arguments that the inhibitors may affect the function of other proteins. Vector -based RNAi was used to establish a stable Caco -2 cell line with a persistent knockdown of effl ux transporters (Celius et al, 2004 ;Watanabe et al, 2005 ;Zhang et al, 2009, Darnell et al, 2010Graber -Maier et al, 2010 ). The effective sites of RNAi were selected using siRNA libraries and single siRNAs, and MDR1 stable knockdown Caco -2 cells were constructed using a tRNAval -shRNA expression vector (Watanabe et al, 2005 ).…”
Section: Applications In Identifying New Transportersmentioning
confidence: 99%